2008
DOI: 10.1021/nl802408y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Strain Relaxation of Ge-Core/Si-Shell Nanowire Arrays

Abstract: Analogous to planar heteroepitaxy, misfit dislocation formation and stress-driven surface roughening can relax coherency strains in misfitting core-shell nanowires. The effects of coaxial dimensions on strain relaxation in aligned arrays of Ge-core/Si-shell nanowires are analyzed quantitatively by transmission electron microscopy and synchrotron X-ray diffraction. Relating these results to reported continuum elasticity models for coaxial nanowire heterostructures provides valuable insights into the observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
142
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(157 citation statements)
references
References 22 publications
14
142
1
Order By: Relevance
“…Nevertheless, our results are in qualitative agreement with those presented by Ramos et al. 59 about SiGe nanocrystals and by a lot of theoretical and experimental observations about other SiGe systems, [60][61][62][63][64][65][66] where the most common structures are Ge core / Si shell nanostructures. ͑The size of the experimental SiGe systems is one order of magnitude bigger than the size of our wires; so the comparison has to be considered only as a qualitative one.…”
Section: Structural Stability and Formation Enthalpysupporting
confidence: 93%
“…Nevertheless, our results are in qualitative agreement with those presented by Ramos et al. 59 about SiGe nanocrystals and by a lot of theoretical and experimental observations about other SiGe systems, [60][61][62][63][64][65][66] where the most common structures are Ge core / Si shell nanostructures. ͑The size of the experimental SiGe systems is one order of magnitude bigger than the size of our wires; so the comparison has to be considered only as a qualitative one.…”
Section: Structural Stability and Formation Enthalpysupporting
confidence: 93%
“…The x-ray diffraction data are, therefore, consistent with the observation of misfit dislocations in these core-shell nanowires by TEM. As previously described, 14 the most likely cause of misfit dislocations in core-shell wires in which Si(Ge) shell deposition is not performed in the presence of HCl is preferential dislocation nucleation at regions of enhanced strain (concave surface curvature) on the roughened wire surfaces. …”
Section: Core-shell Nanowire Strain Characterizationmentioning
confidence: 75%
“…The critical conditions for the formation of the final relaxed configurations that are circular misfit dislocation loops around the cores in core-shell nanoparticles and in the cross sections of core-shell nanowires were calculated in Refs. [54,55,57,58] and [31,33,[35][36][37]41,50], respectively, while those for straight edge misfit dislocations in the longitudinal sections of coreshell nanowires were calculated in Refs. [28,33,35,51,52], in bi-nanolayers in Refs.…”
Section: Modelsmentioning
confidence: 99%
“…[70] and references therein). In bulk core-shell nanowires, Goldthorpe et al [37] observed HREM images of the loops of extrinsic stacking faults bounded by Frank sessile dislocations which could be formed by climb from the shell surface as illustrated by Fig. 2(b).…”
Section: Modelsmentioning
confidence: 99%